The Relationship Between Knowledge of Early Detection and Women's Awareness of Cervical Cancer Screening in Lubang Buaya East Jakarta - Ragilita, Raisha Athaya; Samaria, Dora (Universitas Andalas, 2025)
The high frequency of cervical cancer among women is a concern in Indonesia. Cervical cancer prevention involves two approaches: primary prevention through Human Papillomavirus (HPV) vaccination and secondary prevention through early detection. Women's knowledge is important because the better knowledge about early detection will influence women to do early detection. This study aimed to examine the correlation between knowledge of early detection and women's awareness of cervical cancer screening in Lubang Buaya. This study employed quantitative research methodologies using a cross-sectional design. The sampling method was purposive sampling which recruited a total of 234 married women aged 30-50 years residing in Lubang Buaya. The instruments used in this study were Knowledge about Cervical Cancer Screening Questionnaire and Cervical Cancer Awareness Measure (CAM) Questionnaire. The Chi-square test was performed to analyze the data. The results revealed a significant correlation between the two variables, as indicated by a p-value of less than 0.001 (p < 0.05). A correlation exists between knowledge of early detection and women's awareness of cervical cancer screening.